From Rebellion to Riots - Nasser Tolba (Research in Social Sciences and Technology- OpenED Network, 2018)
This article aims to explore the phenomenon of political violence at Egyptian universities after the downfall of the Muslim Brotherhood regime on June 30, 2013. It is a critical analysis to identify the underlying causes and factors leading to this excessive violence and its impact on the Egyptian universities. The article drew on qualitative methods by interviewing 16 Muslim Brotherhood students from four public universities. The results indicate that frustration, injustice, the collapse of democracy, and interference of the security in universities played an initial role in the students violent behaviors. The forms of violence varied from clashes, throwing stones, and destroying university facilities and infrastructure. The effects of violence on the university were large such as, cancelling study several times, eliminating student political and cultural activities, infrastructure losses, and many arrests, injuries and victims between students and staff. Keywords: 30 June events 2013, political violence, Egypt revolution, student protests.